Modernizing Tourism Access: Online Ticketing at Tahura Banjarmasin as a Practical Solution - latif, Abdul; M. Ulil Albab; Ratna Lindawati (INSTALL: Information System and Technology Journal, 2025)
This research addresses the development of an online ticket booking system for Tahura (Forest Park) Banjarmasin, a premier natural tourism destination in South Kalimantan, Indonesia. The current manual ticket booking system creates operational inefficiencies, including long queues, time delays, and difficulties in visitor management. This research aims to design and develop an effective online ticket booking system to enhance visitor convenience and improve operational efficiency for park management. The research employs diverse methodological approaches including Use Case Analysis, Persona Development, Focus Groups, Workflow Analysis, and Prototyping to ensure comprehensive system development. The proposed system enables tourists to purchase tickets remotely through digital platforms, reducing physical queues and providing transparent information access. The research demonstrates that implementing an online booking system can significantly improve visitor satisfaction, streamline operations, increase revenue potential, and support sustainable tourism development.